Performance analyses of spatial diversity and beamforming for wireless communication systems - Abdul Waheed Umrani (2008)
The desire to achieve high spectrum efficiency and high data rate transmission for wireless communication system has led to the developments of advanced signal processing techniques. Among these, an attractive approach is the use of antenna arrays (smart antennas). The wireless system performance is often limited by signal fading and interference from other co-channel users. Both these effects can be reduced by the use of antenna arrays with the appropriate signal processing and combining of the received signals. In this work, we analyze the performance, in terms of outage capacity and the bit error rate (BER), of multiple antenna arrays in digital mobile communication systems, considering both the uplink and the downlink. Both the uniform linear array (ULA) and uniform circular array (UCA) geometry configurations at the base station are considered in the analysis. This work can be divided in two parts. The first part deals with the characterization of a vector channel model. Since, the performance of wireless communications is limited by signal fading, it is important characterize channel models that reasonably approximate the propagation environment. An extension to the existing work to include multi-input-multi-output (MIMO) channel model is provided. Specifically, the system performance is function of fading correlation matrix, which in turn depends on number of factors such as, the propagation environment which includes the angle spread, and the angle-of-arrival energy distribution, and the array geometry. The expressions for spatial fading correlation matrix is derived for truncated Gaussian, truncated Laplacian energy distributions for both ULA and UCA. These analytical expressions are simple, easy to compute, and are a useful tool in analyzing the performance of multiple antenna communication systems. In the second part, we analyze the performance of a transmit diversity, a receive diversity, and a beamformer systems. It is shown that the system performance for a transmit diversity, a receive diversity, and a beamformer is function of the eigenvalues of the fading correlation matrix. For the downlink cellular communication system, a comparative analysis and the tradeoffs between transmit diversity and beamforming system is presented. The effect of angle spread, angular pdfs, and array perturbations on the performance of both the systems is taken into account. The analytical and simulation results are provided, which are very useful and guide an engineer to design better antenna array systems for various propagation scenarios. The results show that the transmit diversity system using linear arrays or circular arrays do not perform well at small angle spreads. In the extreme case, where fading is completely correlated, the transmit diversity performs no better than a single antenna. It also shows that the transmit diversity system with truncated Laplacian AOA, perform better even at smaller angle spreads as compared to other energy distributions. Further, ULA seems preferable configuration than UCA for transmit diversity systems.